2014
DOI: 10.1016/j.ijintrel.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Universalism and anti-Muslim sentiment

Abstract: a b s t r a c tSocial scientists debate the nature of the critique of Islam that has recently become prominent in various European societies. Some consider it as a mere focussing of more general feelings of xenophobia on a new target group, and therefore regard it as an expression of Islam phobia. Others see it as, at least in part, the result of a defence of values and rights that should be universal. This paper seeks to gauge the extent to which anti-Muslim feelings can be considered the consequence of gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 31 publications
0
28
0
1
Order By: Relevance
“…And several studies have shown that anti‐Muslim sentiment is closely related to other types of prejudice, like ethnocentrism (Van Bohemen et al. ), cultural and economic xenophobia (Elchardus and Spruyt ), and other general measures of prejudice and authoritarianism (de Koster et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…And several studies have shown that anti‐Muslim sentiment is closely related to other types of prejudice, like ethnocentrism (Van Bohemen et al. ), cultural and economic xenophobia (Elchardus and Spruyt ), and other general measures of prejudice and authoritarianism (de Koster et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…And several studies have shown that anti-Muslim sentiment is closely related to other types of prejudice, like ethnocentrism (Van Bohemen et al 2011), cultural and economic xenophobia (Elchardus and Spruyt 2014), and other general measures of prejudice and authoritarianism (de Koster et al 2010). Second, using the dichotomous "Muslim as neighbor" item, we conducted a linear probability multilevel analysis to check whether the results from the extended scale are comparable with the responses to the dichotomous variable.…”
Section: Journal For the Scientific Study Of Religionmentioning
confidence: 99%
“…• studies discussing the role of stereotypes in interethnic conflicts and miscommunication across nations (Verevkin, 2009;Minyar-Belorucheva & Pokrovskaya, 2012;Mishlanova & Sirotkina, 2013;Malkova, 2007;Gladkova, 2013bGladkova, , 2015Petrova et al, 2014;Contini, 2013;Elchardus & Spruyt, 2014;Loennqvist et al, 2014;Ivanic, Bates & Somasundaram, 2014, and others) • studies focusing on issues of in-group and out-group trust and the impact of trust and other psychological phenomena upon interethnic relations (Alesina & La Ferrara, 2002;Abanes, Scheepers & Sterkens, 2014;Gundelach, 2014;Bahry et al, 2005;Allwood, Traum & Jokinen, 2000, and others) • studies identifying social prerequisites for interethnic confrontation, such as the degree of diversity in the society (Alesina & La Ferrara, 2002;Gladkova, 2013a;Matsaganis, Katz & Ball-Rokeach, 2011;Vartanova, 2005Vartanova, , 2012 and the role of social categorization in provoking conflicts and misunderstanding (Ufkes et al, 2012) • studies examining personal characteristics and their role in multicultural communication, including respondents' pride in belonging to a certain ethnic group and its influence upon their tolerance toward other ethnic formations (Ward et al, 2006), as well as individuals' level of education, income, and gender and age characteristics, etc. ; • studies discussing issues of migration and the lack of sense of belonging among migrants as a potential risk factor in a multiethnic society (Osin & Konstantinov, 2014;Bazhenova et al, 2015); • studies analyzing the role of language and linguistic means, including hate speech, in affecting attitudes toward ethnic groups (Shulumba, 2013;Malkova, 2007).…”
Section: * Corresponding Author E-mail: Gladkova_a@listrumentioning
confidence: 99%
“…In connection with this there are a growing number of scientific researches dedicated to the problem of inter-ethnic and inter-confessional relations lately (Banks, 1996;Elchardus & Spruyt, 2014;Harris, 1998;Schaafsma & Williams, 2012).…”
Section: Introduce the Problemmentioning
confidence: 99%
“…Thus, M. Elchardus and B. Spruyt (2014) have investigated the problem of expansion of anti-Muslim sentiment in the world. J.…”
Section: Introduce the Problemmentioning
confidence: 99%